GE_GERICHTE P/1775/2019 vom 4. Mai 2020 - GE Cour de justice (2020)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT;CONTRAINTE SEXUELLE;PORNOGRAPHIE;CONTRAINTE(DROIT PÉNAL);EXPULSION(DROIT PÉNAL);TORT MORAL | CP.187; CP.189; CP.197; CP.181; CP.66abis; CO.49